Geothermal Energy: The Energy of the Future? - Duque, Maria Rosa (2012)
Geothermal Energy: The Energy of the Future? Maria Rosa Alves Duque Abstract —This paper starts by presenting the values obtained for the heat loss of the Earth through the surface to the atmosphere and the sources of this heat. We conclude that the thermal energy of the Earth is immense. Then we write about the different uses of geothermal energy. We present the different types of geothermal plants used in high temperature reservoirs, the binary plants that can use lower temperature fluids, and hot dry rock reservoirs in regions of high heat flux but without geothermal reservoirs. In the direct use of geothermal energy we presents the different types of geothermal heat pumps and how they work. Tables of installed geothermal electric capacity in 2007 and 2010,direct use of geothermal energy in 2005, number of ground source heat pumps installed in 2007 and an estimation for 2008 in European Countries, installed capacity of ground source eat pumps in European Countries in 2008 and HDR or EGS projects shows us who are using geothermal energy and the way it is used. In the environment aspects we show why geothermal is a clean energy. At the end we present some forecasts for geothermal installation in the next years.